All welcome at the show! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
A highlight on the national calendar, the annual Denbigh Agricultural Show will take place in Jamaica from 4 to 6 August 2001. The organisers, CTA partners Jamaica Agricultural Society, are keen to welcome people from the region and other ACP States...